The Role of Perceived Risk in the Adoption of Internet of Things Technology in Sports - Alireza Nazemi Bidgoli; Ehsan Mohamadi Turkmani; Hamid Reza Irani (Shahid Bahonar University of Kerman, 2023)
The Internet of Things (IoT) is one technology that can revolutionize traditional methods and transform sports infrastructure. To promote the adoption of IoT effectively, it's vital for sports manager to understand the factors that positively and negatively affect it. The aim of this study was to investigate how perceived risk impacts people's willingness to use IoT technology in sports. This quantitative study used a survey method and applied a descriptive approach. The statistical population included Iranian athletes, and 394 individuals completed questionnaires using a non-probability sampling method. Data analysis was performed using Smart PLS3 software. Results showed that perceived risk has a direct and negative impact on perceived ease of use, willingness to use, and perceived usefulness. However, its effect on attitude towards use was insignificant. The study also confirmed the positive impact of perceived ease of use on perceived usefulness and attitude towards use. Perceived usefulness had a greater effect on the latter variable. Additionally, perceived usefulness had a significant positive impact on willingness to use IoT technology in sports, as did attitude towards use. Attitude towards use also had a significant positive impact on willingness to use IoT technology in sports. The study recommends implementing strategies to enhance and improve perceived usefulness, ease of use, and attitude towards use while reducing perceived risk to increase acceptance and willingness to use IoT technology in sports.